Endoscopic Diagnosis and Treatment of Iatrogenic Ruptures of the Trachea - A. V. Mironov; S. N. Danielyan; E. A. Tarabrin (Неотложная медицинская помощь, 2022)
Abstract Respiratory tract trauma is not only the result of injuries to the chest and neck, but may be iatrogenic as well. Diagnosis of iatrogenic damage to the trachea is based on data from clinical and instrumental studies. Among the instrumental diagnostic measures, preference is given to early fibrobronchoscopy.The aim of the study is to assess the possibilities of fiberoptic bronchoscopy in the diagnosis of iatrogenic tracheal injuries. Materials and methods. This study analyzed the use of fiberoptic bronchoscopy in 51 patients with suspected iatrogenic damage to the trachea. For iatrogenic ruptures of the trachea, the location on the posterior (membranous) wall and the longitudinal direction (100%), as well as location in the lower and middle thoracic sections of the trachea (71.4%), are typical.Conclusion Bronchoscopy is a direct method for diagnosing this type of damage, which allows the location, size of the defect and tactics to be accurately determined.